Learning from SkeemSaam's involvement in mediating for the Homeless Informal Recyclers in Suburban Parks: a case study of James and Ethel Gray Park and Albert's Farm Parks - Ndovela, Mfundo Ndumiso (My University, 2020)
Suburban residents from Melrose North decided to start a Non-Governmental Organization (NGO) called SkeemSaam to mediate for the homeless informal recyclers that live in suburban parks. Their mediation process takes place between homeless informal recyclers, residents’ associations and various state entities (Sandton Chronicle, 2017). The research that I conducted on the NGO SkeemSaam opens up an area of inquiry into the ways in which civil society organizations such as NGOs mediate for marginalized groups between the state and residents associations. I inquired about the relationships between these actors and how they are negotiated over time. Therefore I ask, “How is SkeemSaam framing its interventions around homelessness in suburban parks while mediating between recyclers, residents associations and agencies of the state?” I used various qualitative research methods to conduct this research. I use the case study research strategy. I use the case study approach because it helped me understand how mediation takes place in different contexts, where there might be different stakeholders. I looked at two case studies in this research which is James & Ethel Grey Park and Albert’s Farm Park. I conducted 9Interviews with various organization or state officials that are part of SkeemSaam’s mediation process such as heads of residents associations, councilors, park managers, Johannesburg Metro Police Department officials, community police forums members, Johannesburg City Park’s officials. I used documents from various platforms such as CUBES-Governance and Parks online database, I further requested documents from organizations that are part of my study including resident associations’ online notices and online media reports. Lastly I undertook direct observations of SkeemSaam’s interventions. I found that SkeemSaam has created a vibrant network between residents associations, informal recyclers and the state. Melrose North Residents and Ratepayers Association and Birdhaven Ratepayers Association seem to have welcomed the SkeemSaam intervention in James and Ethel Gray Park. The informal recyclers that stay in the park have welcomed the SkeemSaam intervention. The informal recyclers are no longer evicted in the park as long as they keep it clean and detect and prevent any criminal elements within the park. Johannesburg City Parks and Zoo general workers in James and Ethel Gray Park give informal recyclers access to sanitation and water facilities. SkeemSaam is able to navigate around residents’ associations in James and Ethel Gray Park because they are from the community. SkeemSaam wasn’t welcomed by the residents in Albert’s Farm Park and they believe that fencing the park will assist in dealing with the homeless informal recyclers. The Friends of Albert’s Farm Park does believe to a certain extent that the SkeemSaam intervention needs to be implemented however the residents from the area still need to be convinced. This research shows that different stakeholders in the different contexts create different pressures for SkeemSaam
A research report submitted to the School of Architecture and Planning in the Faculty of Engineering and Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements of the degree of Masters of Urban Studies, 2020